Study of Fine Motor Skills Among Children With Stunting - Khasanah, Uswatun; Kardia, Cici; Marfuati, Sri (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2024)
A long-term malnutrition is the cause of stunting, a chronic nutritional issue. The development of children's fine motor abilities is negatively impacted. The purpose of this study is to compare the fine motor abilities of children who are stunted and those who are not. Methods: At the Babakan community center in Cirebon, an analytical observational study using a cross-sectional design was carried out. Purposive sampling was used to choose 60 participants for the samples. Data from medical records and questionnaires were used to collect research data. Fisher's Exact test was employed in the analysis. Result: 46.7% of responders are men, 36.7% are between the ages of 52 and 60 months, and 78.3% have adequate fine motor abilities. According to the results of the Fisher's Exact comparison test, toddlers who are stunting and those who are not show significant differences in their fine motor skills (p=0.010, PR 5,500: 95% CI 1,331-22,734). Compared to toddlers without stunting, toddlers with stunting are five times more likely to face delays in the development of their fine motor skills. Conclusion: At the Babakan community center in Cirebon Regency, there are notable disparities in the fine motor skills of toddlers who are stunted and those who are not.